2007
DOI: 10.1002/ajmg.b.30491
|View full text |Cite
|
Sign up to set email alerts
|

The fatty acid amide hydrolase C385A (P129T) missense variant in cannabis users: Studies of drug use and dependence in caucasians

Abstract: A genetic variation in fatty acid amide hydrolase (FAAH), C385A (P129T), has been previously associated with risk for problem street drug use. FAAH is a mammalian enzyme that inactivates neuromodulatory-signaling lipids including the endogenous cannabinoid 1 receptor agonist anandamide. We investigated in adult Caucasians (N = 749) whether this FAAH variant altered the risk for trying, regular use of or dependence on cannabis, alcohol or nicotine, traditional "gateway" drugs. Consistent with our knowledge that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
84
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(94 citation statements)
references
References 33 publications
8
84
0
2
Order By: Relevance
“…Among 80 individuals with drug abuse or alcoholism and over 1000 controls, the odds ratio for risk of combined street drug use and problem drug/alcohol use was 4.9 (95% CI: 2.5-9.7) in rs324420 AA individuals [50], and results were consistent and even more significant in a larger sample with mixed ethnicity [42]. In contrast, the C allele has also been associated with increased risk for progression to cannabis dependence, although this result has not yet been replicated [51].…”
Section: Discussionmentioning
confidence: 90%
“…Among 80 individuals with drug abuse or alcoholism and over 1000 controls, the odds ratio for risk of combined street drug use and problem drug/alcohol use was 4.9 (95% CI: 2.5-9.7) in rs324420 AA individuals [50], and results were consistent and even more significant in a larger sample with mixed ethnicity [42]. In contrast, the C allele has also been associated with increased risk for progression to cannabis dependence, although this result has not yet been replicated [51].…”
Section: Discussionmentioning
confidence: 90%
“…In addition, FAAH mRNA expression in adipose tissue is negatively correlated with circulating endocannabinoid and visceral fat mass, and is increased in mature adipocytes compared with preadipocytes [11][12][13]. A functional missense polymorphism Pro129Thr has been associated with drug use [14][15][16] and with reduced cellular expression and activity of human FAAH in T lymphocytes and COS-7 cells [17]. In addition, the Pro129Thr polymorphism has been associated with overweight and obesity in a cohort of European and African ancestry, but this association was not confirmed in Asian [18] and was borderline associated with overweight in Danish population-based cohorts [19] but in the Key Words Genetics · Obesity · Type 2 diabetes…”
Section: Introductionmentioning
confidence: 99%
“…A missense SNP, C385A (rs324420), results in a mutant form of FAAH with reduced expression and cellular stability (Chiang et al, 2004) and it has been shown that in marijuana users, the C allele of this SNP is associated with a higher risk for progression to cannabis dependence (Tyndale et al, 2007). Also Haughey et al (2008) reported an association between the C allele and craving after marijuana abstinence in young marijuana users.…”
Section: Interaction With Cannabinoid Receptorsmentioning
confidence: 99%